2012
DOI: 10.1159/000342345
|View full text |Cite
|
Sign up to set email alerts
|

Negative Symptoms and Executive Function in Schizophrenia: Does Their Relationship Change with Illness Duration?

Abstract: Background: Negative symptoms and cognitive dysfunction are of crucial functional and prognostic importance in schizophrenia. However, the nature of the relationship between them and the factors that may influence it have not been well established. Aims: To investigate whether the relationship between negative symptoms and executive function changes according to the duration of illness in schizophrenia. Methods: The Positive and Negative Syndrome Scale was used to assess psychopathology and the Wisconsin Card … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 83 publications
2
20
0
Order By: Relevance
“…This observation is partially in line with previous findings. In a recent study, Bagney et al (2013) reported no differences in the non-PE, PE and CAT scores between three groups of patients with different DoI (i.e., up to 5 years, 6-20 years, and more than 20 years). We can speculate that these differences may be secondary to the different temporal subdivision within the patient groups compared with that in the present study (i.e., 10 years).…”
Section: Clinical Characteristics and Behavioral Performancementioning
confidence: 90%
“…This observation is partially in line with previous findings. In a recent study, Bagney et al (2013) reported no differences in the non-PE, PE and CAT scores between three groups of patients with different DoI (i.e., up to 5 years, 6-20 years, and more than 20 years). We can speculate that these differences may be secondary to the different temporal subdivision within the patient groups compared with that in the present study (i.e., 10 years).…”
Section: Clinical Characteristics and Behavioral Performancementioning
confidence: 90%
“…This null result could be due to the chronicity of schizophrenia, particularly considering that these participants had demonstrated greater cognitive impairment (based on the Symbol Coding task), which is consistent with previous literature. 25,26 Duration of illness appears to be an important factor to be considered further when exploring the relationship between PA (and MVPA in particular) and cognitive function. Data presented as n (%), unless otherwise specified.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the relationship between cognitive function and illness duration may not be linear, [24][25][26] and that illness duration is used as an approximation to the stage of illness, 25 the sample was dichotomized on the basis of illness duration using a median split (median = 14. …”
Section: Chlorpromazine Equivalents (Cpz)mentioning
confidence: 99%
“…The relationship between the negative symptom structure and executive functioning may depend on illness duration (Bagney et al, 2013), possibly due to the change in the negative symptoms with illness duration. We assess whether subsets of items provide more stable measurement not across illness phase, but across illness, by testing the invariance of the PANSS within both a full and reduced PANSS.…”
Section: Introductionmentioning
confidence: 99%